2016
DOI: 10.1063/1.4968802
|View full text |Cite
|
Sign up to set email alerts
|

Broadband negative refractive index obtained by plasmonic hybridization in metamaterials

Abstract: Design, fabrication, and measurement of highly sub-wavelength double negative metamaterials at high frequencies J. Appl. Phys. 113, 213712 (2013); 10.1063/1.4809769Broadband and low loss high refractive index metamaterials in the microwave regime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
(41 reference statements)
2
25
1
Order By: Relevance
“…At the microwave frequency regime, the assumption of negligible losses is well supported by previous works. 3234 We use E 0 = 10 7 V/m (intensity ∼13.3 MW/cm 2 ) as the incident electric field amplitude. 9 Superlattices are taken as grown along the z -axis.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…At the microwave frequency regime, the assumption of negligible losses is well supported by previous works. 3234 We use E 0 = 10 7 V/m (intensity ∼13.3 MW/cm 2 ) as the incident electric field amplitude. 9 Superlattices are taken as grown along the z -axis.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…1027 The incorporation of artificial materials with a negative refractive index has led to striking phenomena in photonic superlattices. The so-called metamaterials with simultaneous negative dielectric permittivity (ε B ) and magnetic permeability (μ B ) 2834 yield superlattices with a gap under oblique incident light, i.e., θ ≠ 0, known as the magnetic/electric bulklike plasmon-polariton (PP) gap. The latter originates from the resonant coupling of the magnetic/electric field component of light with the corresponding plasmonlike μ B (ω)/ε B (ω) effective response under transversal electric/magnetic (TE/TM) polarized light, which cannot be observed in all-dielectric superlattices.…”
Section: Introductionmentioning
confidence: 99%
“…They have achieved a lot of research signi¯cance due to the realization of phenomena that cannot be obtained with nature materials. [1][2][3][4] The properties of MMs are derived from the inherent properties of their constituent materials as well as from the geometrical arrangement of those materials. The unique properties of MMs have important applications in superlens, 2 invisible cloaking, 3 antenna, 5 and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, we also have proposed a way to create perfect absorption induced by a cavity in THz frequencies. 24 However, the absorption bandwidth of MPA is relative narrow.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been proposed that novel functions can be realized with metamaterials because of their ability to efficiently and conveniently modulate the properties of electromagnetic waves. During the past years, many research studies based on metamaterials have been reported, such as negative refraction, 2,3 polarization modulation, 4,5 abnormal absorption, transmission and reection. [6][7][8] A metasurface acts as an ultra-thin metallic or dielectric wave front modulator, which can be regarded as the 2D version of metamaterials.…”
Section: Introductionmentioning
confidence: 99%